Pengembangan Video Pembelajaran Animasi Berbasis Powerpoint pada Tema 7 Subtema 1 Kelas IV Sekolah Dasar - Farah Kesuma Jati; Kartono Kartono; Siti Halidjah (AS-SABIQUN, 2023)
This study aims to produce PowerPoint-based animated learning video products that are suitable for use to assist thematic learning activities on the theme 7 sub-theme 1 class IV of elementary school. The method used in this study is a research and development method by adapting the Borg & Gall model. The data sources for this research were 39 grade IV students at SD Negeri 24 Kota Pontianak and 4 expert validators consisting of 2 media experts and 2 material experts. Data collection techniques in this study were interviews and questionnaires. The feasibility of learning video products is in the very good category with an average percentage value of 97.06% in the media aspect and 95.83% in the material aspect. The results of student responses in the small group trial obtained a percentage value of 85.04% in the very good category, and the large group trial obtained a percentage value of 93.35% in the very good category. It can be concluded that PowerPoint-based animated learning videos are very suitable for use as learning media and the use of these learning videos gets very good responses from students.